Pengembangan Buku Ilmiah Populer tentang Struktur Populasi Tumbuhan Pinang (Areca catechu L.) di Sempadan Sungai Aluh Aluh Desa Simpang Warga Kabupaten Banjar - Meydina Hutabarat; Dharmono; Nurul Hidayati Utami (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
The population structure of refers to the presence of a group of plants in a specific area. The pinang (Areca catechu L.) were found along the border of the Aluh Aluh River in Simpang Warga Village, Banjar Regency, which has the potential to serve as a local learning resource through a popular science book. This research aims to describe the population structure of pinang, outline the development process, and describe the validity and readability of a popular science book on the population structure of pinang as a supporting material for plant ecology. The popular science book was developed using Plomp's 3-phase development step: (1) preliminary research analysis, (2) prototyping phase, and (3) assessment phase (Plomp & Nieveen, 2013). The validity was assessed by 2 experts, and readability was tested by five students who had taken Plant Ecology courses. The population structure of pinang along the Aluh Aluh River border revealed a density of 192,85 ind/km² in the pre-reproductive phase, 314,28 ind/km² in the reproductive phase, and 85,7 ind/km² in the post-reproductive phase, with a pitcher or urn-shaped pyramid form. The developed popular science book attained a validity score of 3,59, indicating high validity, and achieved a readability score of 88.33% among students, indicating excellent readability.